Kematangan emosi dan penyesuaian perkawinan pada pernikahan usia muda di Kabupaten Tulungagung - Puput Dwi Mayangsari; Adhyatman Prabowo; Udi Rosida Hijrianti (Cognicia, 2021)
The phenomenon of marriage at a young age is increasing in Tulungagung. Teenagers who decide to marry young will experience some negative impacts, especially if they are not accompanied with a mature emotional state. The purpose of this study was to determine the relationship between emotional maturity and marital adjustment in young marriages. This study uses quantitative methods. Subjects are selected using purposive sampling technique with the criteria of couples who married when their age is less than 21 years old, with a marriage age of 1-5 years in Tulungagung Regency. This study obtained as many as 83 respondents. This study collected data using a scale of emotional maturity and marriage adjustment through google form and then analyzed using the correlation product moment formula. The results showed the value of r = 0.534 (p <0.05) which means that there is a positive relationship between emotional maturity and marital adjustment. The higher the emotional maturity, the higher the marital adjustment. Vice versa, if emotional maturity is low, marital adjustment will also be low.   Keywords: Early age marriages, emotional maturity, marital adjustment